PERANCANGAN RUMAH SUSUN HIJAU DI CENGKARENG DENGAN PENDEKATAN RETHINKING TYPOLOGY DAN TRANSPROGRAMMING - Alexander Jason; Nina Carina (Jurusan Arsitektur dan Perencanaan, 2022)
Jakarta is a city with a very high population density. Every year the population in Jakarta increases by around 88 thousand people according to the Central Statistics Agency for the Special Capital Region of Jakarta in 2020. This is partly due to the high level of urbanization. The high urbanization resulted in the increasing demand for housing. However, the limited amount of land has resulted in higher land prices while the purchasing power of most people for housing in Jakarta has decreased and has led to the emergence of slums. The bad impact of living in slums is the weakening in the quality of health which has a direct impact on the weakening in the standard of living of its inhabitants. Therefore, it is needed flats that not only deal with the problem of slum settlements but also deal with health and economic problems of the residents of the flats so that the standard of living of the community is increasing and has a healthy living environment. The concept of this project is housing that is able to accommodate the lives of Low-Income Communities. This project is a new solution for livable housing that is able to improve the welfare of Low-Income Communities through the main housing program as well as supporting programs for planting areas and independent markets. Residents are expected to be able to live and work in a healthy environment. The design approach uses